2014
DOI: 10.1371/journal.pone.0114283
|View full text |Cite
|
Sign up to set email alerts
|

Health Factors and Risk of All-Cause, Cardiovascular, and Coronary Heart Disease Mortality: Findings from the MONICA and HAPIEE Studies in Lithuania

Abstract: AimsThis study investigated the trends and levels of the prevalence of health factors, and the association of all-cause and cardiovascular (CVD) mortality with healthy levels of combined risk factors among Lithuanian urban population.MethodsData from five general population surveys in Kaunas, Lithuania, conducted between 1983 and 2008 were used. Healthy factors measured at baseline include non-smoking, normal weight, normal arterial blood pressure, normal level of total serum cholesterol, normal physical activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 26 publications
0
24
0
1
Order By: Relevance
“…Interestingly, the differences seen for the statins between the various databases (Table 3) were much greater than seen in previous studies across Europe [1,19], which shows the value of additional research. Not surprisingly, there was convergence in utilization rates between the databases once the reimbursement restrictions were lifted for the statins (Tables 1 and 2) in view of the prevalence of CHD in Lithuania [15]. The lack of any major difference in the utilization of the renin-angiotensin inhibitors between the different databases with no prescribing restrictions in Lithuania (Tables 1 and 4), and similar utilization patterns to Western European countries in 2007 [10,26], further demonstrates that prescribing restrictions can appreciably influence subsequent utilization rates [21,28] and, as a result, demonstrating the need to accurately document ongoing reforms in any CNC study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the differences seen for the statins between the various databases (Table 3) were much greater than seen in previous studies across Europe [1,19], which shows the value of additional research. Not surprisingly, there was convergence in utilization rates between the databases once the reimbursement restrictions were lifted for the statins (Tables 1 and 2) in view of the prevalence of CHD in Lithuania [15]. The lack of any major difference in the utilization of the renin-angiotensin inhibitors between the different databases with no prescribing restrictions in Lithuania (Tables 1 and 4), and similar utilization patterns to Western European countries in 2007 [10,26], further demonstrates that prescribing restrictions can appreciably influence subsequent utilization rates [21,28] and, as a result, demonstrating the need to accurately document ongoing reforms in any CNC study.…”
Section: Discussionmentioning
confidence: 99%
“…Prescribing restrictions and high co-payments for statins in Lithuania limited their reimbursed utilization in 2007 to just 0.8 defined daily doses per 1000 inhabitants per day (DIDs) versus for instance 114.7 in Scotland with no such restrictions [6], despite the prevalence of coronary vascular disease higher in Lithuania than among Western European countries [15]. In addition, prescribing restrictions and high co-payments limited the reimbursed utilization of proton pump inhibitors (PPIs) in Lithuania in 2007 to just 2.3 DIDs in 2007 compared with for instance 76.9 in Scotland with no such restrictions [6].…”
Section: Introductionmentioning
confidence: 99%
“…22 A prospective study found that a low-risk cardiovascular profile was present in only 1% of middle-aged urban adults in Kaunas, Lithuania (1994-2010), with a worsening trend in body mass index, fasting glucose, and healthy diet. 23 Cyprus has very few mortality figures recorded on the WHO database. The few data available, however, show substantial increases in both CVD and IHD, with the exception of female CVD mortality, which demonstrates declining death rates.…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly, over the past decades, mortality due to preventable causes, such as unhealthy lifestyle, was higher in Lithuania than in Western European countries [8]. Important concerns are the risk factors such as smoking, overweight and obesity, unhealthy nutrition habits, as well as physical inactivity [9]. To a great extent, this is attributed to the lack of inter--sectoral public health interventions, particularly in relation to public health and lifestyle changes [3].…”
Section: Health Status Of Older Populationmentioning
confidence: 99%